IT Governance Maturity Assessment at PT PLN Suluttengo Using COBIT 2019 - Tangka, George M. W.; Lumingkewas, Cherry; Lompoliu, Erienika (International Journal of Engineering, Science and Information Technology, 2025)
The rapid development of Information Technology (IT) has made IT governance essential for organizations to align business objectives, manage risks, and optimize resources. PT PLN (Persero) Unit Induk Wilayah Suluttenggo, a key player in electricity distribution in North Sulawesi, Gorontalo, and Central Sulawesi, requires a structured IT governance framework to ensure operational efficiency and compliance. This study evaluates the organization's IT governance maturity using the COBIT 2019 framework, focusing on its Design Factors and Governance Objectives. The research employs a structured methodology, starting with problem identification, a literature review, and the selection of relevant COBIT 2019 domains. Data collection is conducted through structured interviews using the COBIT 2019 Design Toolkit, analyzing ten key Design Factors, including Enterprise Strategy, Risk Profile, IT-related issues, and Compliance Requirements. The findings indicate that PT PLN prioritizes customer service, digital transformation, and regulatory compliance while facing challenges in IT risk management, project execution, and IT investment optimization. Through a detailed assessment of IT governance maturity, this study identifies key gaps and provides recommendations for improvement. Strengthening IT governance practices will enable PT PLN to enhance operational efficiency, mitigate IT-related risks, and align IT initiatives with corporate strategy. The study contributes to both academic research and practical applications by demonstrating the effectiveness of COBIT 2019 in IT governance evaluation.